Relationships between perceived health status and ambient air quality parameters in healthy Japanese: a panel study - Nakao, Motoyuki; Yamauchi, Keiko; Mitsuma, Satoshi; Omori, Hisamitsu; Ishihara, Yoko (BMC Public Health, 2019)
Background There has been growing global concern about air pollution due to its great risk to public health. In Japan, although industrial- and traffic-related air pollution has been decreasing, concerns about particulate matter air pollution has been growing in recent years. In this study, we examined the effects of air pollution on symptoms and the health status of healthy subjects in Japan. Methods Participants ( n = 2887) who visited healthcare centers in Kumamoto or Niigata prefectures in February from 2010 to 2015 were asked to fill out a questionnaire, which was a self-completed booklet containing questions on the characteristics of participants, their respiratory symptoms, and questionnaires on their health status in February, May, and July. Generalized estimating equation analyses were performed to predict the factors associated with the symptoms and health status using two-week averages of air quality parameters obtained from 49 monitoring stations as independent variables. Results Only allergy was associated with air quality in both areas. Prevalence of the other respiratory symptoms were correlated with air quality only in Kumamoto. The health statuses including the ‘physical fitness’, ‘daily activities’, and ‘social activities’ domains were related only to time spent outdoors. The ‘overall health’ was associated with time spent outdoors and concentrations of nitrogen dioxide and suspended particulate matters (SPM) in Kumamoto, and with temperatures and SPM in Niigata. The ‘pain’ score was correlated with temperature and carbon monoxide concentration only in Kumamoto. In Kumamoto, the ‘quality of life (QoL)’ was worse in those who spent shorter hours outdoors, were exposed to lower humidity, higher concentrations of oxidants, SPM, and PM2.5, and who experienced more Asian sand dust (ASD) events. In Niigata, a worsened ‘QoL’ was associated with time spent outdoors, temperature, and SPM. Conclusions The associations between air quality and the health status was found mainly in the comprehensive domain of the health status such as ‘overall health’ and ‘QoL’. The effect of short-term exposure to larger particles, such as SPM, on health status was observed when compared to smaller particles such as PM2.5 and gaseous pollutants.